Design of rockets and space launch vehicles - Edberg, Donald L.; Costa, Guillermo (Reston, Virginia : American Institute of Aeronautics and Astronautics, Inc., 2020)
"Interest is growing in space activity, and many new launchers are in development. Design of Rockets and Space Launch Vehicles is a timely and comprehensive exposé of important concepts and applications. It provides enhanced understanding and exposure to practical aspects of design, engineering, manufacturing, and testing. The subject is mature, but the applications are changing and a new generation of engineers and designers are joining the aerospace industry. Although it is primarily intended for readers with at least a 3rd-year level knowledge of aerospace engineering, mathematics, and physics, because it contains many applications and step-by-step illustrated examples along with photographs or line drawings of actual hardware, it will also be of interest to practicing engineers, technical managers, and others who are interested in "how rockets work" in either the "big picture" sense, or in areas other than one's specialty. This book will answer many questions as to "why things are done this way.""--
Includes bibliographical references and index.
Keywords: Rockets (Aeronautics) -- Design and construction; Launch vehicles (Astronautics) -- Design and construction